Pseudomonas aeruginosa Isolated from the Environment of a Veterinary Academic Hospital in Brazil - Resistance Profile - Schimmunech, Micael Siegert; Lima, Emanuelle Azambuja; Silveira, Ângela Vitalina Barbosa de Assis; Oliveira, Angélica Franco de; Moreira, Cecília Nunes; Souza, Cleusely Matias de; Paula, Eric Mateus Nascimento de; Stella, Ariel Eurides (Acta Scientiae Veterinariae, 2022)
Background: The presence of resistant and potentially virulent bacterial strains in a veterinary hospital environment is a neglected problem. Pseudomonas aeruginosa is an opportunistic microorganism present and circulating in the veterinary hospital environment, of clinical importance and zooanthroponotic transmission of P. aeruginosa has also been reported. The aim of this study was to characterize the population of P. aeruginosa present in a veterinary hospital environment by evaluating their resistance profile and biofilm production. Materials, Methods & Results: A total of 306 samples were collected from the veterinary hospital environment (swabs from consultation tables, surgical tables, door handles, hospitalization cages, stethoscopes, thermometers, and muzzles). The isolates were biochemically identified as belonging to the species Pseudomonas aeruginosa through nitrate to nitrite reduction, motility and oxidase test, growth at 42°C, pigment production, and alkalinization of acetamide. Antimicrobial resistance was tested using the minimum inhibitory concentration (MIC) test. Twenty seven isolates of P. aeruginosa were obtained, with a frequency of 8.8%. The detection of beta-lactamase production and biofilm formation genes by polymerase chain reaction (PCR). Two multidrug resistant (MDR) and 3 single-drug resistant (SDR) strains of P. aeruginosa were identified. Furthermore, it was observed that the strains carried genes related to beta-lactamase production (TEM and CTX-M group 25) and biofilm production (pelA, pslA, ppyR). Discussion: Pseudomonas aeruginosa is considered a major cause of opportunistic hospital infections, as it causes significant morbidity and mortality in immunosuppressed individuals, both in animals and in humans. Veterinary hospitals can harbor microorganisms that cause infections, as well as multiresistant agents. Normally, these environments have a large circulation of people and animals, which particularly enables a facilitated dissemination of these resistant microorganisms. Recently, the World Health Organization (WHO) listed carbapenem-resistant P. aeruginosa as one of 3 bacterial species in critical need for the development of new antibiotics to treat their infections. The data found in this work strengthen the knowledge on the antimicrobial resistance capacity that P. aeruginosa exhibits. The presence of 3 multiresistant strains further highlights the advanced stage of resistance of this bacterial species. The characterization of strains of this species in a veterinary hospital environment is crucial for the control of this population circulating in this environment, and the consequent adoption of more effective measures aimed at controlling its proliferation. The study of this bacterial species in a veterinary hospital environment has a direct impact on human health, due to the mechanisms of resistance and genetic variability that can occur between infections in different animal species and in humans. In view of that, professionals working in veterinary hospitals should be aware of the importance of controlling these microorganisms. Correct measures must be taken to sanitize the environment and utensils between animal care sessions, besides frequent hand washing by all employees and the use of protective equipment such as masks and gloves. The presence of potentially biofilm-producing MDR and SDR strains indicates the free circulation of these bacteria in the veterinary hospital environment. Thus, as a potentially pathogenic microorganism to humans and animals, containment measures must be taken to prevent this possible transmission. Keywords: bacteria, antimicrobial resistance, multidrug resistant, beta-lactamase, biofilm, veterinary care.